Eficiência do melaço como fonte de carbono no sistema de lodo ativado - Oliveira, Gabrielli Lemos de (2019)
As the population increases, water consumption is increasing, so any water taken from the environment for industrial purposes should not be returned to receiving bodies without proper treatment, as it can cause pollution and contamination problems. The present study was carried out in the food industry located in the state of São Paulo. Its activity is the production of gelatin and hydrolyzed collagen. The industry has Effluent Treatment Station (ETE), where the processes are: primary treatment / equalization, coagulation and flocculation, physicochemical, lung tank, biodigester, activated sludge, final clarifier, then the effluent is directed to the river. . The study was conducted in the activated sludge system, one of the main problems in this system is the ammonia nitrogen, when found in high concentrations, if released to water resources, can be excessively unfavorable to the environment. Molasses was tested as a carbon source, being a byproduct of sugarcane production. For molasses application, a reservoir with a capacity of 1000 liters and a metering pump with a flow rate of 1000 L / h were used, which were positioned at the bottom of the tank and routed the molasses into the tanks. The proportion used was 400 liters of molasses diluted in 600 liters of water. Dilution was necessary due to molasses viscosity and metering pump capacity. To analyze the results, an R-Studio statistics program was used to verify the efficiency of molasses application. Averages were made per week from January to June, with a total of 24 weeks, 10 weeks with molasses application and 14 weeks without molasses application, some weeks were not used due to lack of available data. The weeks were separated into two “molasses and no molasses” treatments, using the Tukey test showing whether the means are significantly the same or different. With the results it is possible to observe the average values of the weeks with and without molasses application are close, being possible to affirm that during the periods when there is no molasses application there is greater reduction of the value of ammonia N, that is, the process of denitrification, for the case of this study is more efficient without the application of molasses. During the 10 weeks applied molasses had an average ammonia nitrogen removal efficiency of 64%. Without molasses application, the average ammonia nitrogen removal was 84%. Each parameter that interferes with the nitrification and denitrification process, such as temperature, pH, dissolved oxygen, toxic or inhibitory substances and carbon source was analyzed. Thus, in the present study, through the analysis of the parameters, it was concluded that the activated sludge system with molasses addition was not efficient.